MISIOLOGI DAN PELAYANAN HOLISTIK SEBAGAI DASAR KEPEDULIAN SOSIAL: IMPLEMENTASI PRINSIP YAKOBUS 2:14-17 - Debby Sandra Tendean (Manna Rafflesia, 2024)
This article examines the role of missiology and holistic ministry as the basis of social care with the implementation of the principles outlined in the letter of the Apostle James 2: 14-17. The verses emphasize that faith without works is dead, indicating that real action must accompany true faith. This study aims to provide insights and practical guidance for churches and Christian organizations in carrying out holistic ministry, which not only reaches out to souls but also has a real positive impact on society. Through a missiological approach, this article uses a descriptive qualitative method that has concluded how the church's mission is not only limited to the spread of the gospel but also includes holistic ministry, which means paying attention to humans' physical, emotional, and social needs. First, Christians are expected to be able to understand the theological basis of missiology and holistic ministry in the study of theological analysis of James 2: 14-17 to be able to bring the role of the church in increasing social care and also the practical implications of the principles of James 2: 14-17 in holistic ministry. The holistic ministry emphasizes the integration of evangelism and social action as a manifestation of the Christian faith, which churches and Christian organizations can implement. Thus, missiology-based and holistic ministry meets not only spiritual needs but also physical needs through biblical teachings.